TAKE-OFF HIP EXTENSION ANGLE INFLUENCE ON THE TUCKED BACK SOMERSAULT PERFORMANCE - Deborah Cecilia Navarro Morales; Eduardo Palenque; Jorge Deheza Justiniano (University of Ljubljana Press (Založba Univerze v Ljubljani), 2021)
Back somersault is a basic element of gymnastics; its performance is strongly influenced by the take-off phase. The present work aimed to study how hip extension in the take-off of the tucked back somersault influences the velocity of rotation and the height of t h e somersault. To this end, we recorded a total of 60 somersaults by 4 gymnasts (i.e., 15 somersaults each). There were three groups of somersaults based on the instructions that were given to the gymnasts: no specific instruction, somersault as high as possible and rotate as fast as possible. The records were then analyzed in order to quantify the following variables: maximal height of the mass center and maximal body angular velocity during somersault, the hip angle and the knee angle at the take-off. Gymnasts seemed to be inclined to bend their knees rather than extend their hips in order to carry out the instruction.